Multi-channel Retail and its Integration - Manjee, Rizwan (2007)
As a part of MBA management project, I along with my group selected to undertake a group and individual project. Our group of four was invited into Boots.com to investigate the performance of electrical beauty category using McKinsey retail model as basis. For our individual project, we were supposed to select independent research topics.